A Mild, Fast, and Scalable Synthesis of Substituted α-Acyloxy Ketones via Multicomponent Reaction Using a Continuous Flow Approach - Salvador, Carlos Eduardo M.; Andrade, Carlos Kleber Z. (Frontiers in Chemistry, 2019)
A continuous flow approach for the synthesis of α-acyloxy ketone derivatives from the corresponding arylglyoxals, isocyanides and carboxylic acids is described. The target products were obtained in excellent yields in short residence times and with high purities via the first transcription of the microwave-to-ﬂow paradigm to the isocyanide-based Passerini reaction. Furthermore, this methodology allowed a ten-fold scale-up using the same experimental conditions initially established.